TICTASTIC: behavior recorder for Tourette Syndrome mobile application / Nur Syahirah Rosli - Rosli, Nur Syahirah (2020)
Tics is a type of neurological disorder identifies by repetitive, stereotyped, involuntary gestured and vocalizations called tics. The patient with Tourette Syndrome (TS) are uncomfortable with their repeated and uncontrollable tics which are range widely in their severity, form, frequency and intensity. This project is aiming to create a mobile application which can be used by TS patients to record daily tics frequency. This mobile application is an android-based application. The application is designed and structured using SDLC modelling techniques. By developing this application, it is expected to help the patient to keep on track during recovery process and the recovery process may become much faster and easier.